2006
DOI: 10.1258/096914106776179854
|View full text |Cite
|
Sign up to set email alerts
|

Maternal anxiety following newborn hearing screening: the moderating role of knowledge

Abstract: Objectives: To describe the impact upon maternal anxiety of newborn hearing screening and examine the Possible moderating role of knowledge. Methods: Questionnaires assessing maternal state anxiety, worry and certainty about the baby's hearing, and knowledge about screening, were sent to four groups of mothers three weeks after screening: Group 1 consisted of mothers whose babies had clear responses on a first or second screening test (n=103); Group 2 consisted of mothers whose babies had clear responses on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 24 publications
(22 reference statements)
0
21
0
Order By: Relevance
“…Although some studies have reported an increase of parental anxiety when the infant is screened positive [21], the majority of studies did not report an anxiogenic effect of the announcement of a positive result [22] or any deterioration of the quality of interactions [23]. However, although the level of anxiety measured was only low, parents admit that they are worried about the results obtained on screening tests and are particularly attentive to the way in which their infant responds to various noises [24] and good quality information on the objectives and benefits of newborn hearing screening appears to contribute to a reduction of this anxiety [25][26][27][28]. Furthermore, most of the various published studies used methodologies based on either self-administered questionnaires or telephone interviews, which may have a limited sensitivity as assessment tools to measure the level of parental anxiety and the quality of mother-infant interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Although some studies have reported an increase of parental anxiety when the infant is screened positive [21], the majority of studies did not report an anxiogenic effect of the announcement of a positive result [22] or any deterioration of the quality of interactions [23]. However, although the level of anxiety measured was only low, parents admit that they are worried about the results obtained on screening tests and are particularly attentive to the way in which their infant responds to various noises [24] and good quality information on the objectives and benefits of newborn hearing screening appears to contribute to a reduction of this anxiety [25][26][27][28]. Furthermore, most of the various published studies used methodologies based on either self-administered questionnaires or telephone interviews, which may have a limited sensitivity as assessment tools to measure the level of parental anxiety and the quality of mother-infant interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Scores range from 20 to 80, ‘normal’ being <36 and clinical anxiety >49 19. Existing STAI data (mothers of infants with unilateral (one-sided) hearing referrals and no CMV screening) were used as ‘control’ anxiety data 20. Maternal views on ‘targeted’ newborn screening for cCMV were also sought.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, Watkin et al had made a conclusion that anxiety was low in general whereby less than 1% of the mothers in their study being very worried at the initial test [22]. In a study done by Crockett et al, they have found that the degree of anxiety in hearing screening often seems to be related to the parents' lack of understanding that receipt of no clear responses was unnecessary to mean that the baby had hearing loss [23]. There might be certain group of mothers in our study did not have detail knowledge on UNHS especially as regard to the meaning of the results at each stage.…”
Section: [ ( ) T D $ F I G ]mentioning
confidence: 84%